2011
DOI: 10.1002/ceat.201000367
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Behavior Analyses of Internal Thermally Coupled Air Separation Columns

Abstract: The internal thermally coupled air separation column (ITCASC) is a frontier of air separation energy savings research. The first principles model of the ITCASC is proposed and is based on the material balance, energy balance, and the related thermal coupling relationship which can be used for further control and design studies. The related solution procedures are given. Detailed behavior analyses are carried out. The research results reveal that the ITCASC process has the perfect separation effect and exhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Many researchers carried on analytical research on HIDiC and gained much success [8][9][10][11][12][13][14][15][16]. Then a lot of national projects have applied this technology to the air separation and proved that the heat integrated air separation column (HIASC) could save more energy than the conventional air separation column (CASC) [17][18][19][20][21][22]. Nonetheless, the previous work by our group investigated the behavior analysis of the HIASC process and revealed that the behaviors of HIASC process was quite different compared to the CASC process [22][23][24].…”
Section: Introductionmentioning
confidence: 87%
“…Many researchers carried on analytical research on HIDiC and gained much success [8][9][10][11][12][13][14][15][16]. Then a lot of national projects have applied this technology to the air separation and proved that the heat integrated air separation column (HIASC) could save more energy than the conventional air separation column (CASC) [17][18][19][20][21][22]. Nonetheless, the previous work by our group investigated the behavior analysis of the HIASC process and revealed that the behaviors of HIASC process was quite different compared to the CASC process [22][23][24].…”
Section: Introductionmentioning
confidence: 87%
“…The HPC pressure of a CASC is generally between 0.53 and 0.57 MPa [6,33,35] and the HPC pressure of a HIASC can ideally drop to 0.39 MPa. In this paper, an improved HIASC structure is applied in order to reduce the HPC pressure and the energy consumption.…”
Section: Research Articlementioning
confidence: 99%
“…The condensed feed air 5 is combined with stream 4 and then goes into the HPC. The HPC generally has about 35 equilibrium stages [14,35]. Heat integration is accomplished through heat exchange at the top stages of the two columns, which leads to downward reflux flow for the HPC.…”
Section: Model Descriptionmentioning
confidence: 99%
“…[20][21][22]. These special characteristics bring many difficulties to modeling and controller design, especially for the high-purity columns [13,23,24].…”
Section: Introductionmentioning
confidence: 98%
“…These techniques include essentially thermal coupling between two simple columns where reboiler and condenser are no longer needed, and energy recovery is realized by transferring heat from the rectifying section to the stripping section [11][12][13][14]. Using this technology, the heat integrated air separation column (HIASC) could save 40% more energy than the conventional air separation column (CASC) [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 98%